Pravastatin Protects Against Avascular Necrosis of Femoral Head via Autophagy - Liao, Yun; Zhang, Ping; Yuan, Bo; Li, Ling; Bao, Shisan (Frontiers in Physiology, 2018)
Autophagy serves as a stress response and may contribute to the pathogenesis of avascular necrosis of the femoral head induced by steroids. Statins promote angiogenesis and ameliorate endothelial functions through apoptosis inhibition and necrosis of endothelial progenitor cells, however the process used by statins to modulate autophagy in avascular necrosis of the femoral head remains unclear. This manuscript determines whether pravastatin protects against dexamethasone-induced avascular necrosis of the femoral head by activating endothelial progenitor cell autophagy. Pravastatin was observed to enhance the autophagy activity in endothelial progenitor cells, specifically by upregulating LC3-II/Beclin-1 (autophagy related proteins), and autophagosome formation in vivo and in vitro. An autophagy inhibitor, 3-MA, reduced pravastatin protection in endothelial progenitor cells exposed to dexamethasone by attenuating pravastatin-induced autophagy. Adenosine monophosphate-activated protein kinase (AMPK) is a key autophagy regulator by sensing cellular energy changes, and indirectly suppressing activation of the mammalian target of rapamycin (mTOR). We found that phosphorylation of AMPK was upregulated however phosphorylation of mTOR was downregulated in pravastatin-treated endothelial progenitor cells, which was attenuated by AMPK inhibitor compound C. Furthermore, liver kinase B1 (a phosphorylase of AMPK) knockdown eliminated pravastatin regulated autophagy protein LC3-II in endothelial progenitor cells in vitro. We therefore demonstrated pravastatin rescued endothelial progenitor cells from dexamethasone-induced autophagy dysfunction through the AMPK-mTOR signaling pathway in a liver kinase B1-dependent manner. Our results provide useful information for the development of novel therapeutics for management of glucocorticoids-induced avascular necrosis of the femoral head. Abbreviations： ANFH: avascular necrosis of the femoral head ANFH-PS: avascular necrosis of the femoral head and pravastatin EPCs: endothelial progenitor cells BM-EPCs: bone Marrow derived-endothelial progenitor cells GCs: glucocorticoids Dex: dexamethasone LC3: microtubule-associated protein light chain 3 AMPK: adenosine monophosphate-activated protein kinase mTOR: mammalian target of rapamycin LKB1: liver kinase B1 CaMKKβ: calcium/calmodulin-dependent protein kinase kinase β MRI: magnetic resonance imaging STIR: short-tau inversion recovery LDH: lactate dehydrogenase